2019
DOI: 10.1021/acsearthspacechem.9b00304
|View full text |Cite
|
Sign up to set email alerts
|

The Labile Nature of Ice Nucleation by Arizona Test Dust

Abstract: Dust aerosol is an important atmospheric component due to its ice nucleating ability, which affects cloud phase and precipitation. Arizona Test Dust (ATD) is often used as a proxy for environmental dust aerosol in laboratory studies. In this work, we examine how the ice nucleating behavior of ATD is altered with different solution phase and dry aging processes under several conditions. We find that ATD ice nucleating ability is degraded in significant ways under most conditions, including aging for less than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
62
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 63 publications
5
62
2
Order By: Relevance
“…Thus, the number of publications reporting measurements of INP concentrations in precipitation has increased over the past decade. Numerable insights have been obtained in previous precipitationbased INP studies, including the efficient depletion of INPs relative to other aerosols of similar size in precipitating clouds (Stopelli et al, 2015); constraints on minimum enhancement factors for secondary ice formation processes (Petters and Wright, 2015); and the identification, characteristics and distribution of various INP populations (e.g., Christner et al, 2008;Hader et al, 2014;Stopelli et al, 2017). INP concentrations in precipitation have been used to estimate in-cloud concentrations, based on assumptions that the majority of particles (86 %) in precipitation originate from the cloud rather than the atmospheric column through which the hydrometeor descended (Wright et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the number of publications reporting measurements of INP concentrations in precipitation has increased over the past decade. Numerable insights have been obtained in previous precipitationbased INP studies, including the efficient depletion of INPs relative to other aerosols of similar size in precipitating clouds (Stopelli et al, 2015); constraints on minimum enhancement factors for secondary ice formation processes (Petters and Wright, 2015); and the identification, characteristics and distribution of various INP populations (e.g., Christner et al, 2008;Hader et al, 2014;Stopelli et al, 2017). INP concentrations in precipitation have been used to estimate in-cloud concentrations, based on assumptions that the majority of particles (86 %) in precipitation originate from the cloud rather than the atmospheric column through which the hydrometeor descended (Wright et al, 2014).…”
mentioning
confidence: 99%
“…INPs have been sampled in clouds and precipitation for decades (e.g., Rogers et al, 1998;Vali, 1971Vali, , 1966 to measure abundances, probe their compositions and investigate the extent to which they impact the properties of clouds. There are several caveats to consider when inferring in-cloud INP concentrations or properties from precipitation samples (Petters and Wright, 2015), including sweep-out of additional INPs as the hydrometeor traverses the atmosphere below the cloud (Vali, 1974) and heterogeneous chemistry due to adsorption or absorption of gases (Hegg and Hobbs, 1982;Kulmala et al, 1997;Lim et al, 2010). However, assessing the composition of INPs in precipitation samples is more straightforward than cloud particles.…”
mentioning
confidence: 99%
“…Freezing can be detected optically with manual visual inspection (e.g. Creamean et al, 2018;Hill et al, 2014), with software to detect freezing optically (e.g., Stopelli et al, 2014;David et al, 2019;Perkins et al, 2020;Gute and Abbatt, 2020), with pyroelectrics (e.g., Cook et al, 2020), or with infrared thermal detection (e.g., Zaragotas et al, 2016;Harrison et al, 2018). Each bench-top immersion freezing method has its advantages and disadvantages (Cziczo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Schnell (1977) reported significant losses in fog and seawater samples after storage at room temperature for short periods (6-11 hours). Several studies have reported on the lability of commercially available dust and biological IN entities in storage above 0 ºC or under freezing conditions, including Arizona Test Dust and SnoMax® (Perkins et al, 2020;Polen et al, 2016;Wex et al, 2015), and similar labilities could affect the INPs of similar composition in precipitation samples (Creamean et al, 2013;Martin et al, 2019). Considering the abundance of precipitation based INP https://doi.org/10.5194/amt-2020-183 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this and that INPs < 0.45 μm exhibit significant losses across all storage types, there is a substantial risk that filter-treatments on stored samples in this study would lead to a false conclusion: that the majority of INPs were > 0.45 μm.Previous studies on precipitation collected along the California coast have demonstrated the contribution of dust, marine and terrestrial bioparticles to INPs in precipitation(Levin et al, 2019; Martin et al, 2019). Considering that well-characterized IN-active dust and biological standards (Arizona Test Dust and Snomax®, respectively) are sensitive to storage conditions, it is possible that in situ dust or biological INPs contributed to the observed INP losses Perkins et al (2020). found that the INability of Arizona Test Dust is significantly degraded in most conditions, including aging in deionized water for 1 day, and results fromPolen et al (2016) show that the most efficient (i.e.…”
mentioning
confidence: 99%